A Selective Chromogenic Plate, YECA, for the Detection of Pathogenic Yersinia enterocolitica: Specificity, Sensitivity, and Capacity to Detect Pathogenic Y. enterocolitica from Pig Tonsils. (9th June 2011) - Denis, M.; Houard, E.; Labbé, A.; Fondrevez, M.; Salvat, G.
Abstract : A new selective chromogenic plate, YECA, was tested for its specificity, sensitivity, and accuracy to detect pathogenic Y. enterocolitica from pig tonsils. We tested a panel of 26 bacterial strains on YECA and compared it to PCA, CIN, and YeCM media. Detection of pathogenic Y. enterocolitica was carried out on 50 pig tonsils collected in one slaughter house. Enrichment was done in PSB and ITC broths. Streaking on YECA and CIN was done in direct, after 24H incubation of ITC, after 48H incubation of PSB and ITC. All the plates were incubated at 30 ∘ C during 24 hours. Presence of typical colonies on CIN and YECA was checked, and isolates were biotyped. Pathogenic Y. enterocolitica strains showed an important growth on YECA with small and red fuchsia colonies while biotype 1A exhibited very few violet colonies. Enrichment in ITC during 48H gave the best performance for detecting positive samples in pathogenic Y. enterocolitica, and YECA could detect directly pathogenic Y. enterocolitica strains (2, 3, and 4). Use of YECA in combination with ITC generates a time-saver by giving a positive test in 72H.